The effects of learning style preferences on performance in learning which utilises print-based open learning materials - Abdullah, Syaharom (2000)
This study examined the effects of learning style preferences on the performance in learning utilising print-based distance learning materials.The experimental design was conducted in which 123 randomly selected UUM students were involved.The subjects were involved .The subjects were asked to study a chapter,which has been converted into distance learning format, taken from the textbook for their business report writing course.The subjects were tested on their mastery of the content of the chapter after one week.The learning style preferences of the subjects were determined using an instrument developed by Reid (1987).The study has found that the learning experience is speculated to be the cause.Contrary to the hypothesis.Which hypothesises a positive relationship between preferences for individual and visual learning outcome, the analytical results obtained indicate that only the performance of the three levels of auditory learning style preference are significantly different.To the extent of its reliability, the finding has significant implication for educators in view of the needs to teach more with limited resources.The study, however, is rather limited in scope and a more extensive study is suggested to produce more reliable observations.